Charge effect in the interaction of doxorubicin and derivatives with polydeoxynucleotides - Ruggiero, João [UNESP]; Xodo, Luigi E.; Ciana, Antonio; Manzini, Giorgio; Quadrifoglio, Franco (Elsevier, 1992)
The equilibrium interaction of doxorubicin and its N-acetyl derivative with a series of purine-pyrimidine alternating polydeoxynucleotides has been studied through spectrofluorometry to assess the relevance of the electrostatic contribution to DNA intercalation. The results have shown that: (a) the suppression of the positive charge on the aminosugar has: (I) a profound negative effect on the free energy of intercalation, as expected, and (II) a negligible influence on the base specificity, which supports the notion of an essentially electrostatic effect of N-acetylation on intercalation; (b) a reasonably good accord with the demands of a polyelectrolytic model, due to Friedman and Manning, is found. © 1992.
Keywords: Doxorubicin; Drug-DNA intercalation; Polyelectrolyte effect